Long-term pitch memory for music recordings is related to auditory working memory precision. Issue 4 (April 2018) - Van Hedger, Stephen C; Heald, Shannon LM; Nusbaum, Howard C
Most individuals have reliable long-term memories for the pitch of familiar music recordings. This pitch memory (1) appears to be normally distributed in the population, (2) does not depend on explicit musical training and (3) only seems to be weakly related to differences in listening frequency estimates. The present experiment was designed to assess whether individual differences in auditory working memory could explain variance in long-term pitch memory for music recordings. In Experiment 1, participants first completed a musical note adjustment task that has been previously used to assess working memory of musical pitch. Afterward, participants were asked to judge the pitch of well-known music recordings, which either had or had not been shifted in pitch. We found that performance on the pitch working memory task was significantly related to performance in the pitch memory task using well-known recordings, even when controlling for overall musical experience and familiarity with each recording. In Experiment 2, we replicated these findings in a separate group of participants while additionally controlling for fluid intelligence and non-pitch-based components of auditory working memory. In Experiment 3, we demonstrated that participants could not accurately judge the pitch of unfamiliar recordings, suggesting that our method of pitch shifting did not result in unwanted acoustic cues that could have aided participants in Experiments 1 and 2. These results, taken together, suggest that the ability to maintain pitch information in working memory might lead to more accurate long-term pitch memory.